Case of unrecognised food bone ingestion with dual site intestinal perforations. (21st May 2016) - Coyte, Aishah; Tahar Aïssa, Jamel; Koh, Hoey C; Mackay, Graham
Abstract : Food bone perforation of the bowel is a relatively rare diagnosis. Its presentation is non-specific and often misdiagnosed. We present a case where a food bone perforation in both the large and small bowel was diagnosed on CT scan. A successful outcome was achieved with surgical treatment.